Writing Case Reports Can Improve Seven Components in Clinical Reasoning - Nishizawa T; Ishizuka K; Otsuka Y; Nakanishi T; Kawashima A; Miyagami T; Yamashita S (International Medical Case Reports Journal, 2024)
Toshinori Nishizawa,1,2 Kosuke Ishizuka,3 Yuki Otsuka,4 Toshiyuki Nakanishi,5 Akira Kawashima,6 Taiju Miyagami,7 Shun Yamashita8,9 1Department of General Internal Medicine, St Luke’s International Hospital, Tokyo, Japan; 2Department of Global Health Promotion, Tokyo Medical and Dental University, Tokyo, Japan; 3Department of General Medicine, Yokohama City University School of Medicine, Kanagawa, Japan; 4Department of General Medicine, Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, Okayama, Japan; 5Department of Emergency and General Medicine, Nerima Hikarigaoka Hospital, Tokyo, Japan; 6Department of General Internal Medicine, National Center for Global Health and Medicine, Tokyo, Japan; 7Department of General Medicine, Faculty of Medicine, Juntendo University, Tokyo, Japan; 8Department of General Medicine, Saga University Hospital, Saga, Japan; 9Education and Research Center for Community Medicine, Faculty of Medicine, Saga University, Saga, JapanCorrespondence: Kosuke Ishizuka, Department of General Medicine, Yokohama City University School of Medicine, 3-9 Fukuura, Kanazawa-ku, Yokohama, Kanagawa, 236-0004, Japan, Tel +81-45-787-2800, Fax +81-45-350-2728, Email e103007c@yokohama-cu.ac.jpAbstract: Case reports provide scientific knowledge and opportunities for new clinical research. However, it is estimated that less than 5% of cases presented by Japanese generalists at academic conferences are published due to various barriers such as the complex process of writing articles, conducting literature searches, the significant time required, the reluctance to write in English, and the challenge of selecting appropriate journals for publication. Therefore, the purpose of this opinion paper is to provide clinicians with practical tips for writing case reports that promote diagnostic excellence. In recent years, clinical practitioners have been striving for diagnostic excellence and optimal methods to accurately and comprehensively understand the patient’s condition. To write a case report, it is essential to be mindful of the elements of diagnostic excellence and consider the quality of the diagnostic reasoning process. We (the authors) are seven academic generalists who are members of the Japanese Society of Hospital General Medicine (JSHGM) – Junior Doctors Association, with a median of 7 years after graduation and extensive experience publishing case reports in international peer-reviewed journals. We conducted a narrative review and discussed ways to write case reports to promote diagnostic excellence, leveraging our unique perspectives as academic generalists. Our review did not identify any reports addressing the critical points in writing case reports that embody diagnostic excellence. Therefore, this report proposes a methodology that describes the process involved in writing diagnostic excellence-promoting case reports and provides an overview of the lessons learned. Based on our review and discussion, we explain the essential points for promoting diagnostic excellence through case reports categorized into seven components of clinical reasoning. These strategies are useful in daily clinical practice and instrumental in promoting diagnostic excellence through case reports.Keywords: case reports, clinical reasoning, diagnostic excellence